(untitled) (Journal Of Educational and Psychological Researches, 2024)
This research aims to determine the degree to which the professional license standards for mathematics teachers are reflected in the teaching performance of mathematics teachers in Bisha Governorate. It was limited to the professional educational standards included in the two documents for mathematics teachers (1-2). It used the descriptive survey method. The study sample consisted of 371 female and male mathematics teachers in Bisha Governorate. To collect data, a questionnaire was used, and it consisted of five sections related to professional license standards of mathematics, which are: applying strategies for teaching and learning mathematics; solving mathematical problems and employing their strategies; using mathematical communication and employing its skills in teaching mathematics; employing mathematical modeling and mathematics applications; applying mathematical reasoning and discussing others’ arguments. The validity and reliability of the questionnaire were verified. The study revealed several results, the most notable of which is that the degree of reflection of professional license standards on teaching performance in general is medium, and its mean score is 3.22. The results of the standards were as follows: the standard of applying strategies for teaching and learning mathematics had a mean score of 3.27 and a (medium) degree of achievement; the standard of solving mathematical problems and employing their strategies had a mean score of 3.24 and a (medium) degree of achievement; the standard of using mathematical communication and employing its skills in teaching mathematics had a mean score of 3.24 and a 3.27 degree of achievement; the standard of employing mathematical modeling and mathematics applications had a mean score of 3.16 and a (medium) degree of achievement; and the standard of applying mathematical reasoning and discussing others’ arguments had a mean score of 3.16 and a (medium) degree of achievement. The results also indicated that there are no statistically significant differences between the mean scores of the sample members’ opinions in terms of the study variables (gender, teaching experience, qualification, stage of study, number of times the test was taken). Based on its findings, the study made several recommendations, the most notable of which are as follows: To provide examples and applied models about employing educational theories in teaching and learning mathematics; to train teachers to teach and evaluate mathematical knowledge; and to teach problem-solving.